Trends and correlates of unhealthy dieting behaviours among adolescents in the United States, 1999-2013 - Sarah N. M. Chin; Anthony A. Laverty; Filippos T. Filippidis (BMC, 2018)
Abstract Background The increase in adiposity problems among United States adolescents has been accompanied by persistently high prevalence of unhealthy dieting behaviours (UDBs) such as fasting, taking diet pills/powders/liquids, and vomiting/taking laxatives. This study aimed to examine the associations of self-perceptions of weight status, weight change intentions (WCIs) and UDBs with sex, age and race, as well as trends of UDBs in American adolescents across the weight spectrum. Methods Data come from the biennial cross-sectional, school-based surveys, the Youth Risk Behaviour Surveillance System (1999-2013, n = 113,542). The outcome measures were the self-reported UDBs: fasting for 24 h or more; taking diet pills/powders/liquids; and vomiting/taking laxatives. Sex-stratified logistic regressions assessed relationships between weight status misperceptions across all weight statuses, race and WCIs with UDBs. Differential trends between races were assessed using race*year interaction terms. Results In males, all non-White races had higher odds of fasting and vomiting/taking laxatives than Whites (except fasting in Hispanic/Latinos), with Adjusted Odds Ratios (AORs) between 1.44 and 2.07. In females, Black/African Americans and Hispanic/Latinos had lower odds of taking diet pills/powders/liquids compared to Whites (AORs 0.50 and 0.78 respectively). Racial disparities persisted throughout the study period. Prevalence of fasting and vomiting/taking laxatives did not change between 1999 and 2013 for all races, while taking diet pills/powders/liquids decreased. Compared to individuals of normal weight who were accurate weight status perceivers, individuals of almost all other combinations of weight status and weight status perception had significantly higher odds of displaying any UDB outcome. Overestimation of weight status was found to be the strongest determinant of UDBs. Compared to individuals endorsing "not wanting to do anything" about their weight, individuals endorsing all other WCIs (including wanting to gain weight) also showed significantly higher odds for every UDB outcome, with wanting to lose weight having AORs of the greatest magnitudes. Conclusions Prevalence of UDBs is persistently high, and highest among females across all racial groups. UDBs may elevate undesired weight gain and weight loss in individuals who are obese/overweight and underweight respectively. Further research into weight status perceptions among adolescents may inform efforts to reduce UDBs.